Pemanfaatan Google Earth sebagai Alat Bantu Pembelajaran Sejarah untuk Meningkatkan Prestasi Belajar Siswa - Dewi, Anita Nurmala; Hariadi, Eko (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to examine the use of Google Earth as a history learning tool in improving student learning achievement. Google Earth is a digital map-based application that allows interactive visualization of geographic locations, thus supporting students' understanding of the spatial context of historical events. Through this approach, students are invited to explore historical locations virtually, which not only provides an engaging learning experience, but also deepens their understanding of the subject matter. The results of the study show that the use of Google Earth in history learning can significantly improve student motivation, engagement, and learning outcomes. These findings confirm that the integration of geospatial-based technology in learning can be an innovative solution to improve the quality of history education. Thus, this application offers great potential as an interactive and effective learning medium in connecting historical material with real locations.